English as an academic lingua franca and intercultural awareness: student mobility in the transcultural university. (2nd July 2016) - Baker, Will
ABSTRACT: The increasingly international orientation of many higher education (HE) institutes and the growing role of English as an academic lingua franca have far-reaching implications for how we conceptualise universities and student mobility. In this paper, it is argued that the complexity and diversity of languages, communities and cultures present in many HE institutes mean we can no longer assume a connection between the language of instruction, a local host community and a national culture and language. This is particularly the case in English medium instruction programmes outside of Anglophones settings but also in international universities in Anglophone settings, both of which will be the focus of this paper. The term transcultural university is adopted to reflect this complexity and to move beyond nation-based conceptions of universities. In educating students for mobility in such environments, it is suggested that pedagogy needs to go beyond essentialist language, culture and nation correlations. Intercultural awareness is proposed as a crucial element in preparing students to negotiate the diversity and fluidity of communicative practices in transcultural universities in which mobile students need equally mobile communicative resources.